Exposure to needlestick injury among healthcare support staff in Greater Accra, Ghana: a cross-sectional study - Mary Eyram Ashinyo; Philip Apraku Tawiah; Emmanuel Appiah-Brempong; Paul Okyere (BMJ Public Health)
Objectives This study aims to determine the prevalence and predisposing factors of a needlestick injury (NSI) among healthcare support staff in the Greater Accra region, Ghana.Methods An analytical cross-sectional survey was carried out from 30 January 2023 to 31 May 2023, involving 10 major health facilities. A multistage sampling method was adopted. The data analyses were performed using STATA V.15 software. χ2, Fisher’s exact and Mann-Whitney U tests were used to identify the preliminary association between the outcome variables and predisposing factors. Log-binomial regression analyses were used to confirm factors associated with NSI at a significance level of p<0.05.Results The study was conducted among 149 healthcare support staff. The 1-year exposure to NSI was 68 (45.6%) (95% CI (37.5% to 54.0%)). Being a healthcare assistant (APR=2.81 (95% CI 1.85 to 4.25)), being married (APR=0.39 (95% CI 0.25 to 0.63)), being a supervisor (APR=0.34 (95% CI 0.20 to 0.57)), had training on standard precaution (APR=0.27 (95% CI 0.14 to 0.57)) and non-existence of needlestick reporting system (APR=0.46 (95% CI 0.29 to 0.74)) were significantly associated with NSI.Conclusion The prevalence of NSI was high compared with other regional studies, and the risk factors were related to sociodemographic, behavioural and organisational factors. The study recommends guidelines that are geared towards NSI exposure among healthcare support staff.